SPECIFIC FEATURES OF SELECTING ORGANIZATIONAL DEVELOPMENT STRATEGIES IN THE CONTEXT OF DIGITAL TRANSFORMATION - Sobirjonov Samandar Murodil ugli; Yusupov Ulugbek (TADQIQOTLAR, 2026)
Abstract Digital transformation has fundamentally altered the competitive landscape within which enterprises formulate and execute organizational development strategies. This article examines the specific features that distinguish strategy selection under digital disruption from conventional pre-digital paradigms. Drawing on classical frameworks - including the Resource-Based View, Dynamic Capabilities theory, Porter’s Generic Strategies, and the Balanced Scorecard - the article develops a five- stage Digital Strategy Selection Model and a Digital Strategy Positioning Matrix. The analysis is grounded in empirical data from Uzbekistan’s tourism sector, with reference to ’SKY LUX TRAVEL’ LLC, whose 791.8% revenue growth between 2022 and 2024 illustrates how digital capabilities generate sustained competitive advantage.